2006
DOI: 10.1128/cvi.00267-06
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Oral Administration of Butyrivibrio fibrisolvens MDT-1 on Experimental Enterocolitis in Mice

Abstract: Butyrivibrio fibrisolvens MDT-1, a butyrate-producing strain, was evaluated for use as a probiotic to prevent enterocolitis. Oral administration of the MDT-1 strain (10 9 CFU/dose) alleviated the symptoms of colitis (including body weight loss, diarrhea, bloody stool, organic disorder, and mucosal damage) that are induced in mice drinking water that contains 3.0% dextran sulfate sodium. In addition, myeloperoxidase (MPO) activity levels in colonic tissue were reduced, suggesting that MDT-1 mitigates bowel infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Meanwhile, those key phylotypes that were positively correlated with MS phenotypes may consist of potentially harmful bacteria, and they were, for the most part (26 out of the 34), decreased. For example, the probiotic strains enriched one or more key phylotypes of Bifidobacterium , Olsenella , Barnesiella , Allobaculum and Butyrivibrio that were previously associated with alleviated MS or were shown to prevent dextran sulfate sodium-induced inflammation ( Ohkawara et al , 2006 ; Zhang et al , 2010 , 2012b ; Le Roy et al , 2012 ). Conversely, probiotic treatment reduced key phylotypes within Desulfovibrionaceae , Oscillibacter and Clostridium XIVa that were implicated in the development of obesity-related metabolic disorders ( Zhang et al , 2010 ; Lam et al , 2012 ) or include pro-inflammatory bacterial species ( Tuovinen et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, those key phylotypes that were positively correlated with MS phenotypes may consist of potentially harmful bacteria, and they were, for the most part (26 out of the 34), decreased. For example, the probiotic strains enriched one or more key phylotypes of Bifidobacterium , Olsenella , Barnesiella , Allobaculum and Butyrivibrio that were previously associated with alleviated MS or were shown to prevent dextran sulfate sodium-induced inflammation ( Ohkawara et al , 2006 ; Zhang et al , 2010 , 2012b ; Le Roy et al , 2012 ). Conversely, probiotic treatment reduced key phylotypes within Desulfovibrionaceae , Oscillibacter and Clostridium XIVa that were implicated in the development of obesity-related metabolic disorders ( Zhang et al , 2010 ; Lam et al , 2012 ) or include pro-inflammatory bacterial species ( Tuovinen et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of those, 18 genera showed higher abundance in one rat genotype versus the other. Of the nine genera with higher abundance in BB-DR, three genera, Bifidobacterium, Lactobacillus and Pseudobutyrivibrio , have representatives with known probiotic activity (Silva et al , 1987; Vandenbergh 1993; Jack et al , 1995; Bernet-Camard et al , 1997; Lorca et al , 2001; Reid et al , 2003; Leahy et al , 2005; Ohkawara et al , 2005; Fukuda et al , 2006; Ohkawara et al , 2006; Salminen et al , 2006; Čepeljnik et al , 2003, 2007). These observations from pyrosequencing were verified by qPCR of Bifidobacterium and Lactobacillus .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies document a protective effect for probiotic strains on animals infected with campylobacters. For example, administration of the butyrate-producing Butyrivibrio fibrisolvens, strain MDT-1 to mice both before and throughout the course of infection with C. coli reduces enterocolitis and weight loss (Ohkawara et al, 2006). Two studies have reported the efficacy of mixed probiotics preparations in inhibiting both pathogen shedding and colonization of C. jejuni in 1-day-old chicks (Morishita et al, 1997;Willis & Reid, 2008) and another study describes a reduction in C. jejuni colonization of immunodeficient and immunocompetent mice with combination probiotic therapy (Wagner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%